Eulerian-Lagrangian Approach Evaluation for Numerically Prediction of Fluidized Bed Hydrodynamics - Afrooz, I.E. (Institute of Electrical and Electronics Engineers Inc., 2019)
The main motivation for using fluidized beds in gasification is their excellent gas-fuel mixing ability that cause isothermal conditions and low operating temperature. Understanding the fluidized bed hydrodynamics and flow regime is the key to address the issues of poor gas-fuel mixing. In the current work, a fluidized bed is modeled and studied using ANSYS fluent 15. For this purpose, Eulerian-Lagrangian (EL) approach is chosen to simulate the fluidized bed gasifier hydrodynamics. In this method, the fluid is considered as continuum phase by solving the Navier-Stokes equations. Moreover, particles are treated as dispersed phase and being solved by Lagrangian trajectory calculations including coupling with the continuous phase. To include particle-particle interactions, the Discrete Element Model (DEM) as part of Discrete Phase Model (DPM) capability is also used. Simulation and experimental results are then presented and compared. The results showed that the EL approach can predict well the gas-solid mixing hydrodynamic behavior. Considering the fluidized bed particle movements and bed pressure, a good agreement was observed between computational fluid dynamics and the experimental results. Therefore, it can be concluded that the Eulerian-Lagrangian simulation approach can accurately predict the fluidized bed hydrodynamics. Â© 2019 IEEE.